PERKAWINAN BEDA AGAMA: DISHARMONI NORMA HUKUM DI INDONESIA - Likuwatan, Rauf; Abubakar, Fatum (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
This article discusses interfaith marriages and the occurrence of disharmony in Indonesian legal norms. Disharmony arose because it received legitimacy from several District Courts based on the legal norms contained in the Elucidation to Article 35 letter (a) of Law no. 23 of 2006 concerning Population Administration. Even though the legal norm of Article 2 paragraph (1) of Law no. 1 of 1974 concerning Marriage prohibits interfaith marriages which are not in line with Pancasila norms as a grundnorm. The writing method used is normative juridical through the statue approach and conceptual approach models. The research results show that the norms of Article 35 letter a in Law no. 23 of 2006 has been considered a lex specialist by District Court judges so that it allows interfaith marriages even though it threatens Pancasila norms as the highest norms and SEMA No. 23 of 2006. 2 of 2003 is a special regulatory regulation for judges so as not to legitimize interfaith marriages, then the path of constitutional review or judicial review is to end this disharmony.